2020
DOI: 10.1111/aos.14582
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the phaco chop and drill‐and‐crack techniques for phacoemulsification of hard cataracts: A fellow eye study

Abstract: To quantify the intraoperative parameters and postoperative outcomes after using the phaco chop technique in one eye and drill-and-crack technique in the other eye in patients with bilateral dense brunescent cataract. Methods: The Lens Opacities Classification System III grading system was used to select 132 eyes of 66 patients with bilateral nuclear opalescence (NO) grade NO4 or grade NO5. One eye in each patient with bilateral dense brunescent cataract was subjected to phacoemulsification using the phaco cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…27 Previous studies have reported a 5% to 16% decrease in corneal endothelial cell density after cataract surgery in the first few postoperative months; however, in this study, the decrease was 0.9%, 1.0%, and 5.3% in the Grade II, III, and IV groups, respectively, with no significant difference after 19 weeks in all groups. 18,19,21,24–26,28 These results indicate that the 8-chop technique may be advantageous in surgical invasion of the intraocular tissue.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…27 Previous studies have reported a 5% to 16% decrease in corneal endothelial cell density after cataract surgery in the first few postoperative months; however, in this study, the decrease was 0.9%, 1.0%, and 5.3% in the Grade II, III, and IV groups, respectively, with no significant difference after 19 weeks in all groups. 18,19,21,24–26,28 These results indicate that the 8-chop technique may be advantageous in surgical invasion of the intraocular tissue.…”
Section: Discussionmentioning
confidence: 83%
“…[18][19][20][21][22][23][24] Even in cases with hard lens nuclei, the Lance-chop technique can be completed in less than 10 minutes, which may be shorter than the phaco-chop technique, which reportedly takes 12 minutes. 25 The 8-chop technique had a lower phaco time and CDE than other techniques; it also had an extremely low volume of fluid, that is, one-third to one-fourth of that used for other techniques. [18][19][20][21][23][24][25][26] In particular, the use of a low volume of fluid means that ultrasound and irrigation/aspiration tips are inserted into the eye for a short period, which may have little impact on ocular tissues other than corneal endothelial cells.…”
Section: Discussionmentioning
confidence: 98%
“…The analysis revealed the surgeon used the reverse chopper to perform lens splitting manually without ultrasound energy. In contrast, excessive US energy was required to form a deep crater to bury the needle into the endonucleus for nucleus fragmentation in phaco-chop group ( 5 , 22 ). These results were consistent with the previous reports during grade IV hard nucleus cataract surgery, small pupil cataract surgery and high myopia associated cataract surgery in our eye center ( 16 - 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, phacoemulsification surgery is the standard treatment for cataract and lens fragmentation is considered the critical step in the surgery ( 3 ). In recent years, several different lens splitting techniques in phacoemulsification have been developed, such as in situ fracture, divide-and-conquer, stop-and chop, and phaco-chop techniques, among which phaco-chop is the most classic and popular one ( 4 , 5 ). However, the learning curve of phaco-chop nucleotomy technique is long, as it requires good hand-foot coordination from the surgeon and frequent conversion between ultrasound (US) and negative pressure ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…If a patient received bilateral surgery, only data from the left eye was included for analysis. Of them, 25 eyes that received manual prechop to split the nucleus before phacoemulsification were included in the prechop group, and 29 eyes that received phaco-chop [ 18 ] during cataract surgery were included in the control group. All patients were fully informed of the possible risks of the surgery after finishing preoperative medical examinations.…”
Section: Methodsmentioning
confidence: 99%